Soil contamination from non-sanitary waste landfill in Langat Water Catchment Area, Malaysia - Syed Ismail, Sharifah Norkhadijah; Che Fauziah , Ishak; Abu Samah, Mohd Armi; Mohd. Hatta, Erneeza; Abdul Wahab, Aini Syuhaida (SCIENCEDOMAIN international, 2015)
Soil is a complex matrix and a major reservoir of contamination. It has the ability to bind many potential toxic elements such as heavy metals and they can exist in various forms. Leachate triggered soil contamination in waste landfill through sorption and migration process. This study determined heavy metals contamination in the soil of non-sanitary landfills in Langat river water catchment area in Selangor. Topsoil samples were collected from four landfill sites and three nonlandfill sites for comparison. Soil type, soil pH, organic matter and exchangeable cations were determined using specified method. Available heavy metals in soil samples were determined using Ethylenediaminetetraacetic acid (EDTA). The distribution of heavy metals across landfill sites were performed using ArcGIS. Statistical Package for the Social Sciences (SPSS) statistical software was used to analyse the finding. The overall findings have indicated that Al (2340±575 mg/kg), Fe (2110±330 mg/kg), Cu (65.1±29.6 mg/kg) and Cd (4.99±1.3 mg/kg) were very high in the agriculture soil. Al and Fe also were high in the residential area soils with the mean ± SD of 2760±128 mg/kg and 1620±710 mg/kg respectively. Other elements such as Mn, Zn and Pb were highly detected in waste landfills. The highest Mn and Zn were detected in landfill site B with the mean ± SD of 76.5±13.9 mg/kg and 17.8±24.0 mg/kg respectively. High concentration of Pb was detected in landfill site D (37.9±37.8 mg/kg) and site B (37.5±24.3 mg/kg) while Cd was high in landfill site A (4.61±0.6 mg/kg) and site D (4.39±1.0 mg/kg). Ni was commonly detected as low in all sites. The highest Ni concentration was determined in landfill site B (1.55±3.06 mg/kg). In conclusion, all heavy metals in the studied soils were within the soil standard except for Cd and Cu. Most of heavy metals were retained at the boundary of the landfills. The mobility of heavy metals in the soil was possibly associated with the acidic-pH soils environment, high organic matter and clay content. In conclusion, the soil contamination occurred in both landfills and non-landfill sites where Cu contamination was found in agriculture soil, residential area and landfill site A while Cd contamination was present in all study sites.